Colon classification - Prasad, Anirudh (Shree, 2005)
Contents of material: 1/ Introduction. 2/ Dr. S. R. Raganathan's contributions to library science. 3/ Canons and principles of colon classification. 4/ Facet analysis. 5/ Faceted classification and information retrival. 6/ Faceted classification in information system architecture. 7/ Faceted classification in special subject. 8/ Colon classification and indexing language. 9/ Faceted classification in electronic era.